V.I. Chernyshev as Researcher of Russian Punctuation - K. Ya. Seagal (Научный диалог)
A generalization of the experience of research by Corresponding Member of the USSR Academy of Sciences V.I. Chernyshev (1867-1949) on Russian punctuation is presented. The polemic of V.I. Chernyshev with contemporary scientists A.M. Peshkovsky and G.O. Vinokur on the problems of punctuation is considered. The role of V.I. Chernyshev in the development of punctuation theory in Russian linguistics is shown. The relevance of the study lies in the fact that V.I. Chernyshev’s punctuation concept, which is the first experience of a functional approach to punctuation, is fully described. The novelty of the study lies in the fact that the analysis of segregation as a punctuation phenomenon is assessed. We found textual explanations for those uses of punctuation marks that are significant for the author’s style. The textual understanding of punctuation is revealed, the main principle in teaching punctuation is discussed. According to V.I. Chernyshev, the choice of a punctuation mark is based on semantics, correlated with the tradition of expressing a certain meaning by means of punctuation in the book language and with the aesthetic task of the author. V.I. Chernyshev’s ideas about the interaction of the author’s stylistics and textual criticism in the work of the editor on the punctuation of the artist of the word are described. Special attention is paid to individual examples of V.I. Chernyshev’s analysis of the use of punctuation marks in the works of A.S. Pushkin.